Classifying the Authenticity of Evaluated Smartphone Data - (:unkn) unknown (My University, 2019)
Advances in smartphone technology coupled with the widespread use of smartphones in daily activities create large quantities of smartphone data. This data becomes increasingly important when smartphones are linked to civil or criminal investigations. As with all forms of digital data, smartphone data is susceptible to intentional or accidental alterations by users or installed applications. It is, therefore, essential to establish the authenticity of smartphone data before submitting it as evidence. Previous research has formulated a smartphone data evaluation model, which provides a methodical approach for evaluating the authenticity of smartphone data. However, the smartphone data evaluation model only stipulates how to evaluate smartphone data without providing a formal outcome about the authenticity of the data.This chapter proposes a new classification model that provides a grade of authenticity for evaluated smartphone data along with a measure of the completeness of the evaluation. Experimental results confirm the effectiveness of the proposed model in classifying the authenticity of smartphone data.
Keywords: African Research